2022
DOI: 10.3389/fmed.2022.888050
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis progression in a cohort of young HIV and HIV/ HBV co-infected patients: A longitudinal study using non-invasive APRI and Fib-4 scores

Abstract: BackgroundThe risk of liver fibrosis increases over time in HIV and HIV-HBV individuals even under antiretroviral treatment (ART), warranting a rigorous and periodic monitorization. Given the lower availability of transient elastography, we aimed to assess the longitudinal variation of two non-invasive liver fibrosis scores, APRI and Fib-4, in cases with HIV monoinfection, HIV-HBV co-infection and individuals with HBsAg-seroclearance.MethodsWe performed an observational retrospective study between 2013 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Thus, the condition of being naïve was associated with a higher probability of having detectable viremia after six months of follow-up compared to experienced people who already responded to treatment and in whom cART was previously optimized; (c) having higher HIV RNA at baseline, as already found in a previous work of the MaSTER cohort [7], pointing out the importance of carefully monitoring these people for HIV RNA, even those using DTG-containing regimens, who may run the risk of low level viremia after six months of treatment [14]; (d) FIB4 score > 3.25. Regarding this finding, the correlation between poor cART adherence and increased values of FIB4 score is known to grow in the eventuality of there being detectable viremia in people with liver fibrosis [15]. These findings provide further support to improve medical interventions and counseling with the aim of improving cART adherence in this population, minimizing the risk of virological failure.…”
Section: Baseline Cancer Diagnosismentioning
confidence: 61%
“…Thus, the condition of being naïve was associated with a higher probability of having detectable viremia after six months of follow-up compared to experienced people who already responded to treatment and in whom cART was previously optimized; (c) having higher HIV RNA at baseline, as already found in a previous work of the MaSTER cohort [7], pointing out the importance of carefully monitoring these people for HIV RNA, even those using DTG-containing regimens, who may run the risk of low level viremia after six months of treatment [14]; (d) FIB4 score > 3.25. Regarding this finding, the correlation between poor cART adherence and increased values of FIB4 score is known to grow in the eventuality of there being detectable viremia in people with liver fibrosis [15]. These findings provide further support to improve medical interventions and counseling with the aim of improving cART adherence in this population, minimizing the risk of virological failure.…”
Section: Baseline Cancer Diagnosismentioning
confidence: 61%
“…Recent studies have shown that these scores are reliable noninvasive methods for the assessment of nonsignificant versus significant liver fibrosis in HIV-HBV coinfected patients also [127,128]. A FIB-4 value < 1.5 or APRI < 0.5 are concordant with Fibroscan results and can exclude fibrosis in 94.4% and 96.8% of cases [96].…”
Section: Fibrosis Indexes Based On Serum Biomarkersmentioning
confidence: 83%
“…For each patient, the AST/ALT ratio was measured and APRI and FIB-4 scores were determined using previously reported equations. [ 17 , 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…For each patient, the AST/ALT ratio was measured and APRI and FIB-4 scores were determined using previously reported equations. [17,18] FibroScan 502 (2005), manufactured by Echosens (42Rue Monge 74005, Paris, France), was used in this study. The manufacturer guidelines and findings from previous studies have indicated that 10 valid FibroScan readings are necessary for a test to be deemed successful.…”
Section: Stage Of Fibrosis No (%)mentioning
confidence: 99%